Privileged pioneering in the peripheries : an ethnographic study of Research Capacity Building in the emerging academic disciplines of Irish Nursing and Midwifery - Condell, Sarah L. (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2011)
Research Capacity Building (RGB) was a term often used in research policy literature, including that emanating from nursing and midwifery. However, its meaning was obscure, lacking conceptual and empirical clarity. An initial concept analysis produced an interim definition of the concept of RGB but absent in the literature was any evaluation of the process (as opposed to the product) of RGB or theoretical underpinning of the concept. The literature also lacked any critical comment on RGB from an Irish perspective. Concurrently, an Irish research funding agency, the Health Research Board offered the Clinical Nursing and Midwifery Fellowship scheme aimed at building research capacity and employed a Nursing Research Advisor (NRA) as part of a joint appointment role. The scheme funded experienced nurses and midwives to undertake a PhD that the literature showed was an international benchmark of RGB.
Keywords: Nursing and Midwifery Studies, Ph.D.; Ph.D. Trinity College Dublin